Outcomes of cataract surgery complicated by posterior capsule rupture in the European Registry of Quality Outcomes for Cataract and Refractive Surgery. Issue 8 (August 2022) - Segers, Maartje H.M.; Behndig, Anders; van den Biggelaar, Frank J.H.M.; Brocato, Lucia; Henry, Ype P.; Nuijts, Rudy M.M.A.; Rosen, Paul; Tassignon, Marie-José; Young, David; Stenevi, Ulf; Lundström, Mats; Dickman, Mor M.
Abstract : Refractive and visual outcomes after PCR were significantly worse. PCR increased the probability of receiving a PMMA or no IOL and increased the risk for postoperative complications. Abstract : Purpose: To analyze the outcomes of cataract surgery complicated by posterior capsule rupture (PCR). Setting: European clinics affiliated to the European Registry of Quality Outcomes for Cataract and Refractive Surgery (EUREQUO). Design: Retrospective cross-sectional register-based study. Methods: Data were retrieved from the EUREQUO between January 1, 2008, and December 31, 2018. The database consists of data on demographics, intraoperative complications such as PCR, type of intraocular lens (IOL) material, postoperative refraction, corrected distance visual acuity (CDVA), and postoperative complications. Results: 1 371 743 cataract extractions with complete postoperative data were reported in the EUREQUO. In 12 196 cases (0.9%), PCR was reported. After PCR, patients were more likely to receive a poly(methyl methacrylate) IOL (5.2% vs 0.4%, respectively) or no IOL (1.1% vs 0.02%, respectively) compared with patients without PCR. The refractive and visual outcomes in patients with PCR were significantly worse than in those without PCR (mean CDVA 0.13 ± 0.21 vs 0.05 ± 0.16 logMAR, P < .001; mean absolute biometry prediction error 1.15 ± 1.60 diopters [D] vs 0.41 ± 0.45 D, P < .001). A multivariate linear regression analysis, adjusting for potential explanatory variables, confirmed a statistically significant difference (0.04 logMAR, P < .001, and .70 D, P < .001, respectively). Patients with PCR had significantly more postoperative complications (corneal edema 0.88% vs 0.17%, adjusted odds ratio [aOR], 2.80 95% CI, 2.27-3.45, endophthalmitis 0.11% vs 0.02%, aOR, 4.40 95% CI, 2.48-7.81, uncontrolled intraocular pressure 0.55% vs 0.03%, aOR, 14.58 95% CI, 11.16-19.06, P < .001). Conclusions: Patients with PCR had significantly worse visual and refractive outcomes and more postoperative complications than patients without PCR. However, most of these patients achieved better postoperative visual acuity than that preoperatively.